Identity performance and self-branding in social commerce: A multimodal content analysis of Chinese wanghong women's video-sharing practice on TikTok. (December 2022) - Wang, Yilei; (William) Feng, Dezheng
Abstract: Social media have facilitated the development of a new wanghong profession and the burgeoning social commerce in China, where young women capitalize on their femininity to promote beauty products. Against this background, this study aims to investigate how Chinese wanghong women craft their identities in their self-branding videos on the leading social commerce platform of TikTok. A framework is developed to model their projected identities as evaluative attributes and to elucidate how the identities are constructed using verbal and visual resources. A multimodal content analysis of a corpus of 1258 videos posted by 6 top-ranked wanghong women on TikTok shows that their identities are defined in terms of three marketable attributes: (1) the celebrity self, in which they highlight their glamorous appearance, aspirational lifestyle, and social responsibility, (2) the entrepreneur self, which includes their accentuation of their professionalism and self-empowerment, and (3) the ordinary woman self, in which they emphasize their intimate relationship with their consumer-audience on the one hand, and construct a cheerful and amiable self-image on the other. The multi-faceted identities shed new light on the evolving Chinese femininity shaped by the entangled forces of the development of the neoliberal social commerce and wanghong economy in China on the one hand, and the unique socio-political context on the other hand.